Case Study Elaborated With the Outcome Harvesting Methodology for CCAFS` projects: Climate Site-Specific Management Systems and (CSMS ) and Digital Climate Smart agriculture (D-CSA) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The project manages to generate access to small, medium, and large producers, as well as professionals, technicians, researchers, students, and institutions of 8 different countries of LAM to the benefits of digital technologies through their transformation and democratization. In more than 10 years of experience, it has developed open data-driven agronomy, agronomic, novel analytical tools to improve the yields and Climate Smart decision-making in agriculture of more than 100,000 farmers and extensionists through instruments of data, collection, analysis, and dissemination.